The response of human ectomesenchymal dental pulp stem cells to cisplatin treatment - Seifrtová, M; Havelek, R; Cmielová, J; Jiroutová, A; Soukup, T; Brůčková, L; Mokrý, J; English, D; Rezáčová, M (International endodontic journal, 2012)
AIM: To determine the response of dental pulp stem cells (DPSCs) to DNA-damaging cytostatic cisplatin and compare it with the response of normal human dermal fibroblasts (HDFs). METHODOLOGY: Dental pulp stem cells were exposed to 5, 10, 20 or 40 μmol L(-1) of cisplatin. The proliferation of affected cells was assessed by a Z2 Counter and viability was assessed by means of a Vi-Cell XR using Trypan blue exclusion staining. Cell cycle analysis and induction of apoptosis were performed by flow cytometry. Induction of apoptosis was determined by monitoring the activities of caspases. The expression of proteins was detected by electrophoresis and Western blotting. The descriptive statistics of the results was analyzed by Student's t-test. RESULTS: Dental pulp stem cells had a greater genotoxic stress response to cisplatin compared to HDFs. All three main Mitogen-activated protein kinases (MAPK) families - extracellular signal-regulated kinases (ERK), c-Jun-N-terminal kinase (JNK) and p38 were activated after treatment of DPSCs with cisplatin. The activation of MAPK pathways was not observed in HDFs exposed to cisplatin. The exposure of DPSCs and HDFs to cisplatin provoked an increase in p53 and p21 expression and p53 phosphorylation of serine 15. Higher concentrations of cisplatin reduced the viability of DPSCs and HDFs and induced the activation of caspases 3/7 and 9. CONCLUSION: Dental pulp stem cells had a greater genotoxic stress response to cisplatin compared to HDFs. Cisplatin in higher concentrations triggered activation of MAPK and apoptosis in DPSCs but not in HDFs.
Keywords: Caspase 3; kaspasa 3; Mesenchymal Stem Cells; kaspasa 7; Cell Proliferation; JNK mitogenem aktivované proteinkinasy; ektoderm; p38 Mitogen-Activated Protein Kinases; apoptóza; cytostatické látky; lidé; mezenchymální kmenové buňky; fibroblasty; Ectoderm; Caspase 7; kůže; Humans; Dental Pulp; Enzyme Activation; buněčné kultury; Cell Cycle; proliferace buněk; viabilita buněk; buněčný cyklus; Cytostatic Agents; fosforylace; Cyclin-Dependent Kinase Inhibitor p21; zubní dřeň; extracelulárním signálem regulované MAP kinasy; Apoptosis; JNK Mitogen-Activated Protein Kinases; Caspase 9; Fibroblasts; serin; MAP Kinase Signaling System; Caspase 8; nádorový supresorový protein p53; kaspasa 9; inhibitor p21 cyklin-dependentní kinasy; cisplatina; Cisplatin; Extracellular Signal-Regulated MAP Kinases; Tumor Suppressor Protein p53; aktivace enzymů; Serine; MAP kinasový signální systém; Cell Survival; kaspasa 8; Phosphorylation; Protein Kinase Inhibitors; inhibitory proteinkinas; Mutagens; mitogenem aktivované proteinkinasy p38; Cell Culture Techniques; mutageny; Skin